2019
DOI: 10.1186/s13048-019-0563-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative albumin-to-fibrinogen ratio predicts chemotherapy resistance and prognosis in patients with advanced epithelial ovarian cancer

Abstract: Background: Epithelial ovarian cancer (EOC) is the majority ovarian cancer (OC) type with a poor prognosis. This present study aimed to investigate potential prognostic factors including albumin-to-fibrinogen ratio (AFR) for advanced EOC patients with neoadjuvant chemotherapy (NAC) followed by debulking surgery. Methods: A total of 313 advanced EOC patients with NAC followed by debulking surgery from 2010 to 2017 were enrolled. The predictive value of AFR for the overall survival (OS) was evaluated by receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…A recent meta-analysis by Zhang et al has uncovered the close correlation between FAR and positive lymph node metastasis, distant metastasis, deeper infiltration, and advanced clinical stage in human malignant tumors [33]. Similarly, a recent study by Yu et al indicates preoperative albumin-to-fibrinogen ratio as an independent predictor for chemotherapy resistance and prognosis in advanced epithelial ovarian cancer [34]. All these studies are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…A recent meta-analysis by Zhang et al has uncovered the close correlation between FAR and positive lymph node metastasis, distant metastasis, deeper infiltration, and advanced clinical stage in human malignant tumors [33]. Similarly, a recent study by Yu et al indicates preoperative albumin-to-fibrinogen ratio as an independent predictor for chemotherapy resistance and prognosis in advanced epithelial ovarian cancer [34]. All these studies are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, there are various prognostic parameters which involve albumin in itself such as albumin-globulin, albuminfibrinogen, albumin-bilirubin, prognostic nutritional index. Previous studies established the association of low levels of all these parameters with poor prognosis (22)(23)(24)(25)(26). Taken together, these results establish the prognostic value of albumin either alone or combined with different parameters.…”
Section: Discussionsupporting
confidence: 67%
“…As a marker reflecting coagulation function nutritional and the inflammatory status of patients, several studies have used the fibrinogen-to-albumin ratio (FAR) or albumin-to-fibrinogen ratio (AFR) to evaluate the prognosis of various cancer patients, including those with GC, and have found that increased FAR or decreased AFR levels were associated with poor prognosis in cancer patients (12)(13)(14)(15)(16)(17). Another critical role of FAR or AFR is to assess the effect of the chemotherapy regimen in a particular population to guide the selection of an optimal therapy (18)(19)(20). However, there are currently few reports on the pretreatment FAR being used as a marker to predict progression-free survival (PFS) and overall survival (OS) in patients with GC undergoing first-line chemotherapy.…”
Section: Prognostic Value Of Fibrinogen-to-albumin Ratio In Patients mentioning
confidence: 99%